Immunohistochemical study of janus kinase 1/signal transducer and activator of transcription 3 in psoriasis vulgaris - Farag AGA; Samaka R; Elshafey EN; Shehata WA; El Sherbiny EG; Hammam MA (Dove Medical Press, 2019)
Azza Gaber Antar Farag,1 Rehab Samaka,2 Eman Nabil Elshafey,1 Wafaa Ahmed Shehata,1 Eman Gamal El Sherbiny,3 Mostafa Ahmed Hammam11Department of Dermatology, Andrology and STDs, Faculty of Medicine, Menoufia University, Shebin AlKom, Egypt; 2Department of Histopathology, Faculty of Medicine, Menoufia University, Shebin AlKom, Egypt; 3Dermatology, Andrology and STDs, Ministry of Health, Berkt Alsaba, Menoufia, EgyptBackground: Human JAKs are responsible for generating docking sites for human SSTAT phosphorylation. The role of JAKs in psoriasis pathogenesis has not been clearly explained.Aim: To investigate the role of JAK1 in psoriasis pathogenesis and to assess if this role is mediated through STAT3 or not, through evaluation of their immunohistochemical expression in the skin of psoriatic patients.Methods: This case–control study was carried out on 26 patients presenting with psoriasis vulgaris versus 26 age- and sex-matched apparently healthy volunteers. Psoriasis Area and Severity Index (PASI) scores were used to evaluate psoriasis severity. From all controls and cases (lesional and perilesional), skin biopsies were taken for histopathological and immunohistochemical JAK1 and STAT3 evaluation.Results: There was significant stepwise upregulation of JAK1 from controls to perilesional to lesional psoriatic skin of the patient group in both epidermis and dermis (P≤0.001 for both). Dermal JAK1 H-score was significantly associated with psoriasis severity (P=0.01). STAT3 was significantly overexpressed in lesional psoriatic skin over nonlesional skin (P<0.001). There were significant positive correlations between lesional H-scores for STAT3 and Psoriasis Area and Severity Index scores in epidermis (r=0.63, P<0.001), and in dermis (r=0.47, P=0.04). There was a significant positive correlation between JAK1 and STAT3 expression in epidermal lesional psoriatic skin (r=0.44, P=0.03).Conclusion: JAK1 has a proinflammatory effect in psoriasis pathogenesis, which could be mediated through increasing STAT3 expression in psoriasis. JAK1 and STAT3 tissue expression could be markers of psoriasis severity. JAK1 may be used as a target for immunotherapy in psoriasis-management programs.Keywords: JAK1, STAT3, psoriasis, immunohistochemistry